2020
DOI: 10.1063/5.0031568
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of field emission from copper electrodes with inclusion of oxygen surface layer and work function changes based on first-principles calculations

Abstract: Analysis of field emission requires the inclusion of the internal potentials that shape the electronic wavefunctions and tunneling probabilities; details of the work function that are dependent on material quality and defects; and the role of the density of states (DOS) that influences the electronic supply. Here, these factors are collectively included on the basis of density functional theory to obtain predictions of field-dependent electron tunneling current densities. Results are obtained in copper for thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Furthermore, because of the high oxygen content in the sputtered films, the electrons’ film will be strongly bounded to the oxygen because of the greater electronegativity of the oxygen; as a result, it makes the thermionic emission of electrons more difficult. Theoretical calculations have shown that the workfunction of the Cu-O system is larger than that of pure copper [ 57 ]. The experimental results show that both the barrier height and the effective Richardson constant decreased.…”
Section: Ohmic Contact In the Nanoscalementioning
confidence: 99%
“…Furthermore, because of the high oxygen content in the sputtered films, the electrons’ film will be strongly bounded to the oxygen because of the greater electronegativity of the oxygen; as a result, it makes the thermionic emission of electrons more difficult. Theoretical calculations have shown that the workfunction of the Cu-O system is larger than that of pure copper [ 57 ]. The experimental results show that both the barrier height and the effective Richardson constant decreased.…”
Section: Ohmic Contact In the Nanoscalementioning
confidence: 99%
“…The semiconductor work function (W s ) has the same definition as the metal work function. Due to the n-i-p type model structure proposed in this study, the contact potential difference between the back metal electrode and the p-type semiconductor (Cu 2 BaSnS 4 ) can be expressed as follows [71].…”
Section: Analyzing the Effect Of Working Temperature And The Back Ele...mentioning
confidence: 99%
“…As the distance (D) between metals and semiconductors decreases, a space charge region will appear on the surface of the semiconductor, and surface potential (V s ) will be formed on the surface and inside of the semiconductor. Therefore, the above equation can be changed to the following form [71].…”
Section: Analyzing the Effect Of Working Temperature And The Back Ele...mentioning
confidence: 99%